Model Perilaku Pasien Pada Aplikasi Berbasis Kesehatan Menggunakan Metode Design Thinking - Adrian, Qodhli Jafar; Styawati, Styawati; Rifai, Jefri Andri (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
The COVID-19 pandemic has had a significant impact on health, economy, and society in Indonesia. In dealing with the pandemic, the term New Normal emerged, namely a change in behavior to continue normal activities by implementing health protocols. One of the innovations that has developed in this digital era is a health-based application designed to increase the accessibility of health services, such as online consultations, health monitoring, medication reminders, and health education. However, the success of this application depends not only on technology, but also on a deep understanding of patient behavior as users. Understanding patient needs, preferences, and challenges is important to create an optimal user experience. Without this, health applications are at risk of not being widely adopted. This study uses the Design Thinking method to understand patient behavior and design relevant solutions. With stages such as empathy, problem definition, ideation, prototyping, and testing, this study aims to design a patient behavior model in health-based applications. This approach is expected to provide a comprehensive picture of the factors that influence patient behavior, as well as help developers create applications that are more intuitive, effective, and in accordance with user needs in the era of the pandemic and new habits.